Etnomatematika pada Permainan Congklak - Sili, Agustina Somi; Towe, Mariana Marta (Indo-MathEdu Intellectuals Journal, 2024)
Ethnomathematics is a mathematical concept contained in a culture. The concept of ethnomathematics can support cultural preservation based on daily activities, customs, and traditional knowledge. This research aims to find out the process of playing congklak and describe the elements of mathematics in the congklak game in Adonara. This research uses qualitative research with an ethnographic approach. The subjects in this  study were 5 people, namely 1 resource person and 4 children who played congklak. The data collection techniques used were observation, interview and documentation. The main instrument in this research is the researcher himself. The auxiliary instruments are observation guidelines and interview guidelines. The results of the study obtained mathematical elements in the game of congklak, namely counting operations (multiplication, subtraction and addition), flat shapes (square, rectangle and circle), space, half a ball